2003
DOI: 10.1007/s000110300028
|View full text |Cite
|
Sign up to set email alerts
|

Histamine uptake into non-neuronal brain cells

Abstract: IntroductionThe main function of various transport systems is to maintain the cellular concentrations of the physiological substances. However, transport also contributes to various mechanisms in clearing and scavenging substances from the interstitial spaces. In the CNS, the termination of many neurotransmitters involves rapid removal from the synapse; mainly by uptake either into presynaptic terminal or into the surrounding glia through specialised transport systems.Histamine (HA) is a regulator of the vascu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 13 publications
(19 reference statements)
0
11
0
Order By: Relevance
“…Rat astrocytes were capable of significant histamine uptake, but rat synaptosomes did not have histamine transport activity. In addition to these in vitro experiments, Huszti et al demonstrated that astrocytes played a crucial role in the clearance of brain histamine in vivo (Huszti, 1998(Huszti, , 2003Huszti et al, 1998). In addition to these in vitro experiments, Huszti et al demonstrated that astrocytes played a crucial role in the clearance of brain histamine in vivo (Huszti, 1998(Huszti, , 2003Huszti et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Rat astrocytes were capable of significant histamine uptake, but rat synaptosomes did not have histamine transport activity. In addition to these in vitro experiments, Huszti et al demonstrated that astrocytes played a crucial role in the clearance of brain histamine in vivo (Huszti, 1998(Huszti, , 2003Huszti et al, 1998). In addition to these in vitro experiments, Huszti et al demonstrated that astrocytes played a crucial role in the clearance of brain histamine in vivo (Huszti, 1998(Huszti, , 2003Huszti et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Among glial cells astrocytes have been proposed to be the main histamine inactivation site [6]. Reports from Huszti´s laboratory described bidirectional [7][8][9] histamine uptake into cultured glial cells prepared from embryonic chicks [7] and neonatal rats [8][9][10] which was Na + -but not Cl --dependent [11]. Glial cells were also found to be involved in the continuous removal of neuronal histamine from the synaptic cleft in in vivo conditions [12].…”
Section: Introductionmentioning
confidence: 99%
“…Reports from Huszti's laboratory described histamine uptake by cultured glial cells prepared from embryonic chicks [10] and neonatal rats [11][12][13], which was Na + -dependent [14] and bidirectional [10,12]. In order to demonstrate histamine uptake into cultured glial cells, astrocytes from neonatal (P0-P6) rats required maintenance in culture for at least 19 days [11,14].…”
Section: Introductionmentioning
confidence: 99%